A critical analysis of codon optimization in human therapeutics - Mauro, Vincent P.; Chappell, Stephen A. (Trends in molecular medicine, 2014)
•Codon optimization is a gene engineering approach to increase protein production.•Assumptions underlying codon optimization approaches may be invalid.•Codon optimization for nucleic acid therapies presents potentially unique hazards.•Hazards can arise by disrupting or introducing overlapping functions in mRNAs. Codon optimization describes gene engineering approaches that use synonymous codon changes to increase protein production. Applications for codon optimization include recombinant protein drugs and nucleic acid therapies, including gene therapy, mRNA therapy, and DNA/RNA vaccines. However, recent reports indicate that codon optimization can affect protein conformation and function, increase immunogenicity, and reduce efficacy. We critically review this subject, identifying additional potential hazards including some unique to nucleic acid therapies. This analysis highlights the evolved complexity of codon usage and challenges the scientific bases for codon optimization. Consequently, codon optimization may not provide the optimal strategy for increasing protein production and may decrease the safety and efficacy of biotech therapeutics. We suggest that the use of this approach is reconsidered, particularly for in vivo applications.